مدى توفر سمات القيادة التحويلية لدى رؤساء الأقسام و نوابهم دراسة ميدانية بكلية العلوم الاجتماعية بجامعة عمار ثليجي بالأغواط - عبد التواب عبيرات; سعيد بن دشو; محمد بوفاتح (My University, 2021)
This study aimed to reveal the availability of transformational leadership behaviors among department heads and deputies at Ammar Tleji University in Laghouat, Faculty of Social Sciences. To achieve the objectives of the study: a questionnaire for the study was prepared to collect primary data from the research sample estimated at 110 male and female employees, and we distributed the questionnaire to a number of male and female employees estimated at 56 questionnaires, and this is in order to achieve the objectives of the study and reach real results. The search results found: First: The level of availability of transformational leadership behaviors with its dimensions (ideal influence, motivation, individual legality, intellectual arousal) is high at the University of Laghouat. Second: And that there are no differences in the level of availability of transformational leadership among the workers of Ammar Thaleji University due to the gender variable. Third: There are no statistically significant differences in the level of availability of transformational leadership among the workers of Ammar Thaleji University due to the variable of seniority. Fourth: And from there, there are no statistically significant differences in the level of availability of transformational leadership among the workers of Ammar Thaleji University due to the department variable. Thus, the importance of leadership appears as a social, administrative necessity, and it constitutes a total return to the administrative process, as it is not possible to expect the success of any administrative work without it. Rather, successful leadership is a source of the success of the organization, as the responsibility of leadership crystallizes in its ability to formulate cooperation in order to unify the efforts of subordinates in pursuit of achieving Leadership goals, meeting the needs of employees and achieving the multiple functional goals of the organization